Multiple ways to promote adult grass carp (Ctenopharyngodon idella) muscle hypertrophy: Application of dietary myo-inositol - Meiqi Wang; Lin Feng; Pei Wu; Yang Liu; Hongmei Ren; Xiaowan Jin; Xiaoqiu Zhou; Weidan Jiang (Animal Nutrition)
Skeletal muscle constitutes the largest tissue in fish and represents the primary edible portion. Given the substantial differences in muscle growth dynamics between fish and mammals, fish serve as a crucial and distinctive model organism for investigating the fundamental mechanisms of growth regulation in vertebrates. Myo-inositol (MI), originally discovered in muscle, plays significant biological roles in growth regulation, membrane biogenesis, and transmembrane signal transduction. However, to date, no studies have investigated how MI affects adult fish growth and muscle development. A total of 450 adult grass carp (Ctenopharyngodon idella) (704.84 ± 0.91 g) were randomly divided into 6 treatments with 3 replicates of 25 fish each to receive dietary MI at 35.38 (basal diet, deficient group), 98.12, 195.21, 292.30, 389.39, and 486.48 mg/kg. The trial period lasted for 8 weeks. Results indicated that compared with the 35.38 mg/kg MI group, all groups supplemented with MI improved the specific growth rate (SGR) and percent weight gain (PWG) of adult grass carp (P < 0.05). Compared with the deficient group, the sodium-myo-inositol cotransporter 2 (SMIT2) and MI content in the muscle of grass carp in the 292.30 to 486 mg/kg MI group were significantly elevated (P < 0.05). Compared with the deficient group, the dietary MI levels of 195.21 to 486.48 mg/kg lead to increased myofiber mean diameters and the frequency of myofibers with a diameter > 100 μm, while decreased myofiber diameters < 60 μm (P < 0.05). This implies that MI promotes muscle hypertrophy. The hypertrophic effect of MI was primarily ascribed to an increase in the number of myonuclear and enhanced protein synthesis, which is associated with the regulation of the skeletal muscle lysyl oxidase (LOX) and the protein kinase B (AKT)/target of rapamycin (TOR)/ribosomal protein S6 kinase 1 (S6K1) signaling pathways. Additionally, MI inhibited the myostatin (MSTN) and the forkhead box O3 (FoxO3)/muscle RING-finger protein-1 (MuRF1)/muscle atrophy F-box (MAFbx) pathways, which are involved in muscle atrophy and protein degradation. Based on PWG, the appropriate MI requirement of adult grass carp was determined to be 301.30 mg/kg. This study offers a preliminary theoretical foundation for the potential mechanism by which MI promotes muscle hypertrophy in fish and furnishes a reference for the commercial feed formulation of adult grass carp.